Mg(II) Selective PVC Membrane Electrode Based on Methyl Phenyl Semicarbazone as an Ionophore. (21st January 2013) - Chandra, Sulekh; Sharma, Kusum; Kumar, Adarsh
Abstract : A PVC-membrane-based Mg(II) selective electrode was constructed using methyl phenyl semicarbazone (MPS) as a neutral carrier. The sensor exhibits a Nernstian response for Mg(II) ion over a wide concentration range 1.0 × 10 - 8 to 1.0 × 10 - 1 M with the slope of 28.4 mV/per decade having detection limit 1.7 × 10 - 9 M. It was relatively a fast response time (< 10 s for concentration ≥ 1.0 × 10 - 3 and < 15 s for concentration of ≥ 1.0 × 10 - 6 M) and can be used for 8 months without any considerable divergence in potentials. The proposed sensor revealed relatively good selectivity and high sensitivity for Mg(II) over a mono-, di-, and trivalent cation and can be used in a pH range of 1.0–9.5. It was also successfully used as an indicator electrode in potentiometer titration and in the analysis of concentration of magnesium in various real samples.